Manajemen Psikofarmakologi Untuk Kesehatan Mental - Puput Mulyono (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2026)
Background: Treatment of mental illness with pharmacotherapy is closely monitored in clinical centers. While in most developed countries, this practice is well established.. Objective: The purpose of this study was to analyze and investigate the handling of mentally ill patients at the Mental Health Center. Method: This research methodology uses simple quantitative methods to identify and evaluate prescription quantity and distribution. Result: Of the described drug therapies, while disorders were categorized according to the International Classification of Diseases-10R. According to the clinic, there were no significant changes in the route of drug administration (p > 0.11). Almost, two-thirds of the prescribed drugs were essential (66.1%). Considering the therapeutic drug classes, more than half were antipsychotics (53.2%), while the percentages of 17.2% and 13.8% were anticholinergic drugs and anxiolytics/hypnotics. These drug classes were 84.2% of the total drugs used Conclusion: Conclusions on the use of effective drugs with low safety such as clozapine. The implementation of drug prescribing practices needs to be considered by stakeholders, for future strategies in the selection and provision of psychopharmacology.